Kewenangan Notaris Dalam Melakukan Pengesahan Fotokopi Visum et Repertum Sesuai Dengan Aslinya - Fauzi, Nabyla (PT Matra Cendikia Abadi, 2025)
In the case of the murder of Briptu Yosua, the results of observations from the forensic team were validated and made into an authentic deed that could be used as legal evidence. The act of validation (legalization) and making an authentic deed by a notary from the forensic results in the form of a Visum Et Repertum letter raises new problems, namely related to the notary's authority to legalize forensic results that have not been regulated in Notary Law. The purpose of this study is to find the notary's authority in legalizing forensic results and to find the basis for notaries to carry out legalization, as well as the notary's responsibility for the act of legalizing forensic results. This study uses a normative juridical approach. The results of this study are that the forensic results letter is an authentic letter so that the notary has the authority to legalize the forensic results letter and the basis for the notary to legalize the forensic results refers to the provisions of Article 15 paragraph (2) Notary Law, and the notary's responsibility for forensic results that have been validated is that the notary only ensures the forensic results letter of the person who signed the forensic results letter and ensures that the signature on the document is genuine, and the notary also checks that the forensic results letter issued is in accordance with legal procedures.